APAKAH KUALITAS AUDIT MEMODERASI PENGARUH FIRM SIZE DAN COMPANY GROWTH PADA INCOME SMOOTHING? - Arifin, Imam; Wicaksono, Bambang; Wisdaningrum, Oktavima (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2024)
This study aims to analyze the influence of firm size and company growth on income smoothing and the moderating role of audit quality. The population of this study is companies listed on the Jakarta Islamic Index for the period 2020-2022. The analysis was conducted on 36 samples determined based on purposive sampling and analyzed using multiple linear regression and moderated regression analysis (MRA). The study results indicate that company growth has a negative effect on income smoothing, while firm size does not have a significant effect on income smoothing. Other research findings indicate that audit quality does not moderate the effect of firm size or company growth on income smoothing. These results imply that managers need to pay attention to corporate growth to minimize income smoothing, and investors and creditors can consider corporate growth in making investment and credit decisions.